Valproic acid induces prosurvival transcriptomic changes in swine subjected to traumatic injury and hemorrhagic shock. Issue 4 (April 2018) - Georgoff, Patrick E.; Nikolian, Vahagn C.; Higgins, Gerald; Chtraklin, Kiril; Eidy, Hassan; Ghandour, Mohamed H.; Williams, Aaron; Athey, Brian; Alam, Hasan B.
Abstract : BACKGROUND: Valproic acid (VPA) is a histone deacetylase inhibitor that improves outcomes in large animal models of trauma. However, its protective mechanism of action is not completely understood. We sought to characterize the genetic changes induced by VPA treatment following traumatic injuries. METHODS: Six female Yorkshire swine were subjected to traumatic brain injury (controlled cortical impact), polytrauma (liver and splenic laceration, rib fracture, rectus crush), and hemorrhagic shock (HS, 40% total blood volume). Following 2 hours of HS, animals were randomized to resuscitation with normal saline (NS) or NS + 150 mg/kg of intravenous VPA (n = 3/cohort, 18 samples total). Blood samples were collected for isolation of peripheral blood mononuclear cells at three distinct time points: baseline, 6 hours following injuries, and on postinjury day 1. RNA was extracted from peripheral blood mononuclear cells and sequenced. Differential expression analysis (false discovery rate < 0.001 and p value <0.001) and gene set enrichment (Panther Gene Ontology and Ingenuity Pathway Analysis) was used to compare VPA to non–VPA-treated animals. RESULTS: A total of 628 differentially expressed RNA transcripts were identified, 412 of which were used for analysis. There was no difference between treatment groups at baseline. The VPA-induced genetic changes were similar at 6 hours and on postinjury day 1. Upregulated genes were associated with gene expression ( p 2.13E-34), cellular development (1.19E-33), cellular growth and proliferation (1.25E-30), and glucocorticoid receptor signaling (8.6E-21). Downregulated genes were associated with cell cycle checkpoint regulation (3.64E-22), apoptosis signaling (6.54E-21), acute phase response signaling (5.84E-23), and the inflammasome pathway (1.7E-19). CONCLUSION: In injured swine, VPA increases the expression of genes associated with cell survival, proliferation, and differentiation and decreases those associated with cell death and inflammation. These genetic changes could explain the superior clinical outcomes in VPA-treated animals, including smaller brain lesion size and improved neurologic recovery. Abstract : Supplemental digital content is available in the text.